Extractive Fluorimetric Determination of Methoxyethylmercury Chloride in Environmental Samples - Satyaveni, S.; Chandra Rao, G.P.; Seshaiah, K. (Asian Journal of Chemistry, 2016)
A sensitive, extractive fluorimetric method for the determination of trace levels of methoxyethylmercury chloride is described. The method is based on the decomposition of methoxyethylmercury chloride under acidic condition and bromination to form tetrabromomercurate(II) anion. The resulting anion is reacted with rhodamine 6G, a cationic fluorescent dye and the resulting ion pair is extracted into toluene. The fluorescence of the organic layer is measured at 560 nm after excitation at 536 nm. The method is extended to the determination of methoxymercury chloride in environment samples. The method is compared with reported spectrophotometric method and found to be more sensitive.